Power generation in dual chamber microbial fuel cells using dynamic membranes as separators. (1st June 2018) - Li, Xinyang; Liu, Guicheng; Sun, Shaobin; Ma, Fujun; Zhou, Siyu; Lee, Joong Kee; Yao, Hong
Highlights: Performance of dynamic membrane microbial fuel cells (DM-MFCs) has been studied. DM-MFCs achieved a higher maximum power density than an up-flow dual-chamber MFC. DM-MFCs are suitable for enlargement owing to their sleeve-shaped configuration. Dynamic membranes can be used to increase power production in MFCs. DM-MFCs are promising tools for practical applications. Abstract: Two dual-chamber microbial fuel cells (MFCs) that use dynamic membranes as separators were designed for power production. The performance of these dynamic membrane microbial fuel cells (DM-MFCs) was studied. Compared to an up-flow dual-chamber MFC (U-MFC), at the total volume of 1.1 L, DM-MFCs achieved a higher maximum power density (1923 mW m −3 versus 856 mW m −3 ). This is because the DM-MFCs have lower membrane resistance (0.6–5.4 Ω), oxygen diffusion coefficient ( D 0  = 1.8 × 10 −7  cm 2  s −1 ), and cost (0.3 USD m −2 ) than other reported separators; e.g., anion exchange membrane (ACM), cation exchange membrane (CEM), ultrafiltration membrane (UFM), and J-cloth. The dynamic membrane is primarily composed of filamentous bacteria and vorticellidae-like protozoa, which tightly attach to the nylon supporting layer. This microorganism layer consumes most of the dissolved oxygen and prevents oxygen transfer from the cathode chamber to the anode chamber, leading to the low D 0 value of the dynamic membrane. Power production of DM-MFCs was further optimized by increasing the NaCl concentration in the influent and the electrode area. The results show that DM-MFCs are feasible and suitable for scaling-up because of their sleeve-shaped configuration. These results indicate that dynamic membranes can be used to increase power production in MFCs relative to traditional separators and DM-MFCs are promising tools for practical applications.